Attitude Of Corporate Managers And Stockholders With Respect To Good Governance In A Developing Country: A Case Study Of Bangladesh - Z. Mamun, Muhammad; Aslam, Mohammad (Asian Academy of Management (AAM), 2005)
This study showed the perceptional differences between corporate managers1 and stockholders2 regarding good governance. The study is conducted among 25 pairs of senior managers and stockholders from 25 randomly chosen corporations3 in Bangladesh. Different statistical tools like numeric scale, discriminant analysis, descriptive analysis, t-test, F-test were used for the comparative analysis. Regarding good governance, it is found that the corporate managers and stockholders possess opposing view. While managers of the studied firms find governance of their companies is quite well but stockholders view that it is very poor. This happened especially in terms of turnover, production, capital, leverage, debt service, credit policy, solvency, human resource, recruitment, technology, customer satisfaction, internal control, strength, opportunity, competition, industry position, collective bargaining agent (CBA) issues and economic remedies which the study found the groups differ in perception; whereas, they have similar view in terms of adequacy of research fund, company weaknesses and threats, contingency plans, presence of political influence. The managers think that the companies do not have enough retained earnings and these should not be distributed among stockholders, but the stockholders think otherwise. Managers always perceive that they are underpaid whereas stockholders express the opposite view. Each group believes that it is the other group that dominates the decision-making. While both the groups want to have mutual interaction but stockholders want to interact more than the mangers. No doubt this attitudinal differences are not good for smooth functioning of the corporations, what is needed is openness, more dialogues, mutual trust and understanding of each other. The study also noted that corporate managers' tenure is more with the company than a stockholder's holding of stock. It is also found that the managers are better educated than the stockholders. The study observed more male domination both in management position and stockholding of the corporations. Though both of the groups belong to same age level but their distribution shows that the stockholders entering the share market at an early age